Exploring Human 5HT1A/2A Receptor Through Homology Modeling and Flexible Docking Studies for the Binding Hotspot of Substituted 2,4-imidazolidinedione and Oxazolidinedione Derivatives - Dhanawat, Meenakshi; Gupta, Sumeet; Mujwar, Somdutt (Current Indian Science, 2023)
Introduction To obtain the binding site of a model of the human 5-HT1A/2A receptor, a series of substituted 2,4-imidazolidinediones and oxazolidinediones were subjected to flexible docking using GLIDE. Methods The docking scores that were generated are correlated with the in-vivo affinity data that had already been collected. Results When combined with a homology model of 5HT1A/2A, the GLIDE docking approach was based on a template for 2-adrenergic receptors. Conclusion A model for ligand binding in the hydrophobic portion of the binding site was proposed after discussing the impact of the structure and hydrophobic characteristics of the aryl moiety on binding affinities.
Keywords: GLIDE